Brother Odd [compact disc, unabridged] - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2006)
St. Bartholomew's Abbey sits in majestic solitude amid the wild peaks of California's high Sierra, a haven for children otherwise abandoned, and a sanctuary for those seeking insight. Odd Thomas has come here to learn to live fully again. But trouble has a way of finding Odd Thomas, and it slinks back onto his path.